The Concept of Marxism and Its Correlation with Religion - Zarkasyi, Amal Fathullah; Mahbubah, Khotimatul; Saputro, Agus Dwi; Mafaza, Ahmad Tauhid (KALAM, 2022)
The ideology of Marxism that was a response to capitalism is considered a comprehensive view of life. Its emergence in the midst of oppression is seen as a significant solution. In fact, it is called a complete theoretical system. Marx with his ideology endeavour to defend and stop the exploitation of the proletariat caused by the capitalist bourgeoisie. This research is a qualitative library research. Sources of data were obtained from several books, journals and literatures that have relevance to this research. While the analytical method used is a critical analysis method using an Islamic worldview approach. The aim of this study is to explain the concept of Marxism then analyze and criticize it with an Islamic worldview. The results of this study explain that the ideology of Marxism seems to provide a solution but in fact it brings more complex problems. Instead of prospering humans from the alienation of the capitalist system, this ideology actually alienates humans in another way, namely distancing humans from private property which is clearly allowed in Islam. This ideology has even alienated humans from their religion. The conclusion is that Marx is not fundamental in his efforts to provide solutions. He only looks at the economic aspect even though in this life there are various aspects. His solution is partial and does not move integrally as is the case in Islam.